Manajemen Peserta Didik di SD Muhammadiyah Kedunggong - Nisa Salsabila; Dahlia Erviani Putri; Farid Setiawan (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This research aims to obtain student management ideas. This research was carried out at SD Muhammadiyah Kedunggong using qualitative methods with a field study type of research. Technical data collection is carried out through interviews, observation, and also documentation. The research results tell: (1) student planning. (2) coaching students. (3) student evaluation. (4) special student services. Includes: (a) library services. (b) computer lab services. (c) canteen service. (d) prayer room services. Where this service is really needed in schools. Moreover, the prayer room service, because this prayer room is a place for teachers to improve students' religious values.